PARAMETER INTERAKSI BINER KESETIMBANGAN UAP-CAIR CAMPURAN ALKOHOL UNTUK OPTIMASI PROSES PEMURNIAN BIOETANOL (Jurnal Bahan Alam Terbarukan, 2016)
In this work, the binary interaction parameters of vapor-liquid equilibrium for the mixtures of primary alcohols (methanol, ethanol, 1-propanol or 1-butanol) with C5 alcohols were obtained. A total of 15 systems that consisted of isobaric vapor-liquid equilibrium data at atmospheric pressure were selected. The binary interaction parameters were determined as temperature function by correlating the selected vapor-liquid equilibrium data using the Wilson, Non-Random Two-Liquid (NRTL) and Universal Quasi-Chemical (UNIQUAC) activity coefficient models. The binary interaction parameters were described as the temperature-dependent to increase the capability of the parameters for the application in wide range of temperature. The correlation showed good results because the root mean square deviation (RMSD) between the calculation values and experimental data were relatively low. The obtained parameters were very useful for optimizing the distillation column in the bio-ethanol purification process.